Traumatic brachial artery dissection in a pediatric patient: An interdisciplinary approach to care - Katherine Kazen; Jeremy Powers; Steven Hopkins; Brad Feltis (Elsevier, 2022)
Severe traumatic arterial injuries are rarely seen in pediatric patients. Management decisions are often guided by anecdotal experience due to a lack of well documented evidence-based guidelines. This paper demonstrates success with multidisciplinary management and close, structured follow-up in a 5 year old boy with traumatic brachial artery dissection and extensive soft tissue loss.